Childhood in The Grip of Violence and Consumerism: An Empirical Study on Television - Yağbasan, Mustafa; Kurtbaş, İhsan (Ardahan Üniversitesi, 2015)
In the past there were basically two sources of information/influence for children; parents and educators. At the present time, television has also been added to these sources, especially new communication technologies such as social media. The limitations in everyday practices of the children and loss of traditional family role have caused the television both to become a device that forms and creates their individual information and to assume a role almost as “babysitter”. However, the television causes many other physical, psychological and social damages, in addition to its harmful effect to be a model on them and their childhood. The interaction between the children and the television, on the one hand, takes a shape in accordance with the social structures of nations, on the other hand, differs according to the contents of the television broadcasting. Eventually the child (hood) corrupts, loses its distinctive purity and moves away from the genuine values and definitive characteristics at the time it opens to the world outside its own. At that point, the problem is that the mass media exposes the children to violence and consumption by rating concerns. This study bases on some hypothesis that on the ground that there are not any self-control [in the television companies] and control [in the eye of the state-the parents-educational institutions-social service units] mechanisms, or with a more optimistic expression, these mechanisms are insufficient, the childhood is spent in the grip of violence and consumption and the children are more defenseless against the negative effects of the television. Two different techniques were used to investigate these hypotheses. First, a fictitious scenario (sinopse) in which the main theme is violence was told to the children, and an analysis of reception was carried out in relation to their instant responses by means of interviews. The purpose here is to mention how the children consider violence codes on television by understanding how they interpret a fictitious scenario of violence. Second is the implementation of survey in relation to what extent the children recognize the smart signs, how effective the parents are in the television-child interaction, what mass media the children follow and how long, how much space this period takes up in the activities and games and how the children response to the calls of consumption such as advertising. The purpose is to determine the limits of the defense(lessness) for the children relating to the television, advertising in particular. Remarkable results obtained have confirmed the hypotheses; starting from the point of this data, new roadmaps have been formed and various solution proposals presented.

Geçmişte çocukların temel olarak iki tane bilgilenme/etkilenme kaynağı vardı; anne-baba ve eğitimciler. Günümüzde bu kaynaklara başta sosyal medya gibi yeni iletişim teknolojileri olmak üzere, televizyon da eklenmiştir. Çocukların gündelik pratiklerinin çeşitliliğindeki sınırlılık ve geleneksel aile rolünün kaybolması, televizyonu çocuğun bireysel bilgisini oluşturan ve yaratan temel aygıt konumuma getirdiği gibi, adeta ona “bakıcı rolü” de yüklemiştir. Ancak televizyon; bir model oluşturma yoluyla çocuğa ve çocukluğa zarar vermenin yanında, fiziksel, psikolojik ve sosyal daha birçok tahribatlara neden olabilmektedir. Çocuk ve televizyon arasındaki etkileşim bir yandan ulusların sosyal yapılarına göre şekillenirken, öte yandan televizyon yayınlarının içeriklerine göre farklılaşabilmektedir. Neticede çocuk(luk), kendi dışındaki dünyanın bilgisine açıldığı anda, bozulmakta, kendine özgü saflığını yitirmekte ve sahici değerlerinden ve tanımlayıcı özelliklerinden uzaklaşmaktadır. Bu noktada sorun, kitle iletişim araçlarının, rating kaygısıyla, çocukları şiddet ve tüketim sarmalının içine almalarıdır. Bu çalışma oto-kontrol [televizyon kurumlarında] ve kontrol [devlet nezdindeebeveynlerde-eğitim kurumlarında-sosyal hizmet birimlerinde] mekanizmalarının olmaması ya da daha iyimser bir ifadeyle yetersiz olması münasebetiyle çocukluğun şiddet ve tüketim kıskacında tükendiği ve çocukların televizyonun olumsuz etkilerine karşı daha savunmasız oldukları yönünde bazı hipotezlere dayanmaktadır. Bu hipotezleri test etmek üzere iki farklı teknik kullanılmıştır. Birincisi, çocuklara ana teması şiddet olan fiktif (hayali) bir senaryo (sinopsis) anlatılmış ve mülakat yoluyla anlık tepkilerine ilişkin alımlama analizi (recetion analyse) yapılmıştır. Burada amaç, çocukların fiktif bir şiddet senaryosunu nasıl yorumladıklarını anlayarak televizyondaki şiddet kodlarının nasıl alımlandığını analiz etmektir. İkincisi ise akıllı işaretlerin çocuklar tarafından ne kadar tanındıkları, televizyon-çocuk etkileşiminde ebeveynlerin ne kadar etkin oldukları, çocukların hangi kitle iletişim araçlarını ne kadar süreyle takip ettikleri, bu sürenin ders ve oyun etkinlikleri içinde ne kadar yer kapladığı ve çocukların reklam gibi tüketim çağrılarına nasıl tepki verdiklerine ilişkin anket uygulamasıdır. Buradaki temel gaye ise reklam özelinde çocukların televizyona ilişkin savunma(sızlık) sınırlarını tespit etmektir. Elde edilen çarpıcı sonuçlar hipotezleri doğrulamış, bu verilerden hareketle yeni yol haritaları oluşturulmuş ve çeşitli çözüm önerileri sunulmuştur.
Şiddet ve Tüketim Kıskacında Çocukluk: Televizyon Üzerine Ampirik Bir Çalışma